DNA polymerase η is the sole contributor of A/T modifications during immunoglobulin gene hypermutation in the mouse - Delbos, Frédéric (The Rockefeller University Press, 2007)
Mutations at A/T bases within immunoglobulin genes have been shown to be generated by a repair pathway involving the DNA-binding moiety of the mismatch repair complex constituted by the MSH2–MSH6 proteins, together with DNA polymerase η (pol η). However, residual A/T mutagenesis is still observed upon inactivation in the mouse of each of these factors, suggesting that the panel of activities involved might be more complex. We reported previously (Delbos, F., A. De Smet, A. Faili, S. Aoufouchi, J.-C. Weill, and C.-A. Reynaud. 2005. J. Exp. Med. 201:1191–1196) that residual A/T mutagenesis in pol η–deficient mice was likely contributed by another enzyme not normally involved in hypermutation, DNA polymerase κ, which is mobilized in the absence of the normal polymerase partner. We report the complete absence of A/T mutations in MSH2–pol η double-deficient mice, thus indicating that the residual A/T mutagenesis in MSH2-deficient mice is contributed by pol η, now recruited by uracil N-glycosylase, the second DNA repair pathway involved in hypermutation. We propose that this particular recruitment of pol η corresponds to a profound modification of the function of uracil glycosylase in the absence of the mismatch repair complex, suggesting that MSH2–MSH6 actively prevent uracil glycosylase from error-free repair during hypermutation. pol η thus appears to be the sole contributor of A/T mutations in the normal physiological context.